Estudo sobre o hidróxido de potássio no processo de produção industrial de poliol poliéter - Baixo, Rogério Dias (Universidade Federal de São Carlos, 2010)
Metallic ions may interact with polyether polyols giving macromolecular complexes. From this approach, it was investigated the interaction of cationic potassium with polyether polyols by means of several techniques in order to proof complexation as well as its ocurrence. The industrial synthesis of polyether polyols does not result in a pure product but gives a mixture with a range of molecular weights. The preparative chromatography was used to isolate a selection of products with representative molecular weights. The mass spectrometry was used to analyse the chromatographically separated fractions with representative molecular weights. The conductivimetric study of polyether polyols solutions containing potassium ions allowed detection of interactions occurring between the organic molecules and the metallic ions, implying the existence of complexation capacity in the linear ligands. The complexation of the cationic potassium was further confirmed by proton nuclear magnetic resonance. The small angle X-ray scattering (SAXS) spectroscopy allowed the characterization of the size and morphology of the macromolecular complexes. The polyether polyols used in the present study were supplied from DOW Brasil S.A.
Keywords: Polímeros; Complexação; Potássio; Raios-X - espalhamento a baixo ângulo; Poliol poliéter; CIENCIAS EXATAS E DA TERRA::QUIMICA